Perancangan dan Implementasi Website Pembelajaran Berbasis Game Interaktif untuk Anak TK Usia 5–6 Tahun - Addelia Aldha Kharisma; Griselda Tabina Riani; Joko Suwarno (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The integration of information technology in education has encouraged the development of more innovative learning media, including for Early Childhood Education (ECE). This study aims to design and implement a game-based interactive learning website for kindergarten children aged 5–6 years at TK Islam Baiturrahim as a supporting medium for the teaching and learning process. The main problem addressed in this study is the limited availability of digital learning media that can enhance children's interest in learning through interactive and enjoyable activities. The research employed data collection methods, including observation, interviews, and literature review, to identify user requirements and learning needs. The system was developed using HTML, CSS, JavaScript, PHP, and MySQL and was deployed in the XAMPP environment. The website provides features such as student login, a learning dashboard, six educational games, a scoreboard, and an administrator page for managing student data and game results. System testing was conducted using the Black Box Testing method to ensure that each function operated according to user requirements. The testing results showed that all features functioned properly and met the expected system requirements. The implementation of this interactive game-based learning website provides a more engaging learning experience through the concept of learning while playing, assists teachers in delivering learning materials more interactively, and facilitates the monitoring of students' learning outcomes through a score-recording system. Therefore, this website is suitable as a supporting learning medium for early childhood education and can be further developed by adding more learning materials, animations, audio, and a wider variety of educational games.